Segregation by Design: An Analysis of Apartheid-Enabling Constitutional Provisions - Albar, Rafsi Azzam Hibatullah; Kusumadi, Padre Jovianthony; Alfarizi, Rivaldy (Constitutionale, 2024)
This paper critically examines constitutional provisions that facilitate apartheid systems, focusing on how these provisions enable the establishment and perpetuation of segregation and discrimination. Despite global condemnation of apartheid, similar traits persist in various jurisdictions today, notably in Israel's treatment of Palestinians and Myanmar's oppression of the Rohingya. This research investigates the constitutions of South Africa, Israel, and Myanmar to analyze how they legitimize and sustain segregationist regimes. Using a substantive and structural comparative analytical approach, the research identifies common factors that enable apartheid practices, including identity-based citizenship conditions, discriminatory treatment provisions, restrictions on the political participation of marginalized groups, and entrenched power structures. The findings reveal that apartheid-enabling provisions do not always explicitly endorse segregation but often grant broad legislative powers that can be exploited, as seen in Apartheid South Africa. Similarly, the constitutions of Israel and Myanmar provide constitutional protection to select ethnic groups, thereby institutionalizing segregation. The research concludes that four key elements common to the studied constitutions contribute to the maintenance of apartheid systems: differentiated citizenship status, legitimized segregationist practices, limited political participation for certain groups, and entrenched power structures resistant to reform.